Emaranhamento mediado por caos em um ponto quântico aberto via formalismo de Keldysh - Batista, Rafael Alves (2019)
In this dissertation, we investigate universal properties of the electronic transportation in mesoscopic system using chaotic quantum dots, which the geometry of such semiconductors change constantly. We use nonequilibrium quantum field theory (Keldysh formalism) to describe the electronic transport through the quantum dots and to investigate the theoretics consequences in a chaotic case. Following Beenaker’s proposal and performing numerical simulations, we analyze the electronic conductance and shot noise in such devices, comparing with the literature, and the connection between shot noise and quantum entanglement. We also investigate the Bell’s inequality, we show new results which establish a link between the chaos in a chaotic quantum dot and the creation of quantum entanglement.